The cell colony development is connected with the accumulation of embryogenesis-related proteins and dynamic distribution of cell wall components in in vitro cultures of Fagopyrum tataricum and Fagopyrum esculentum - Magdalena Zaranek; Artur Pinski; Bozena Skupien-Rabian; Urszula Jankowska; Kamila Godel-Jedrychowska; Katarzyna Sala-Cholewa; Katarzyna Nowak; Ewa Kurczyńska; Ewa Grzebelus; Alexander Betekhtin (BMC Plant Biology)
Abstract Background Due to the totipotency of plant cells, which allows them to reprogram from a differentiated to a dedifferentiated state, plants exhibit a remarkable regenerative capacity, including under in vitro culture conditions. When exposed to plant hormones, primarily auxins and cytokinins, explant cells cultured in vitro can undergo differentiation through callus formation. Protoplast culture serves as a valuable research model for studying these processes in detail. This knowledge is particularly relevant for improving common and Tartary buckwheat species. To gain deeper insights into the stages of cell development from protoplasts—such as cell division, cell colony formation, and microcalli development—we focused on analyzing proteomes, cell wall composition, and changes in the expression profiles of selected genes in Fagopyrum protoplast cultures. Results The results demonstrate a significant accumulation of somatic embryogenesis-related proteins like late embryogenesis abundant proteins (embryogenic protein-DC-8-like, seed biotin-containing protein) and endochitinases during the developmental path of protoplast-derived cultures. Additionally, we noted an extensive increase in seed storage proteins like vicilin, oleosins, and seed biotin-containing proteins during the culture. Investigation of somatic embryogenesis-associated transcription factors revealed massive up-regulation of LEAFY COTYLEDON1 for the 50th day of F. tataricum protoplast-derived cultures. However, for BABY BOOM, the transcription factor was noted to be down-regulated during the development of cell colonies. Furthermore, we demonstrated the variable distribution of cell wall components like pectin side chains, arabinogalactan proteins (AGPs) and extensins (EXTs), indicating the reorganisation of cell wall composition during the culture period. Conclusions This study revealed changes correlating with regaining embryogenic competence during the development of Fagopyrum protoplast-derived cell colonies. Our findings revealed variable expression levels of genes and proteins associated with somatic embryogenesis. This analysis identified an increase in seed storage proteins that play a significant role in the somatic somatic embryogenesis pathway of regeneration. Furthermore, the relationship between transcription factors and these processes seems to be connected with regaining somatic cells’ totipotency and promoting embryogenic competence of protoplast-derived cell colonies. Additionally, we observed dynamic changes in cell wall composition during the development of the protoplast-derived cultures. Clinical trial number Not applicable.